Overview of the main methods used to combine proteins with nanosystems: absorption, bioconjugation, and encapsulation - Mariagrazia Di Marco (Dove Medical Press, 2009)
Mariagrazia Di Marco1, Shaharum Shamsuddin2, Khairunisak Abdul Razak3, Azlan Abdul Aziz4, Corinne Devaux1, Elsa Borghi1, Laurent Levy1, Claudia Sadun51Nanobiotix, Paris, France; 2School of Health Sciences, Health Campus Universiti Sains Malaysia, Kelantan, Malaysia; 3School of Materials and Mineral Resources Engineering, Engineering Campus, 4School of Physics, Universiti Sains Malaysia, Penang, Malaysia; 5Department of Chemistry, Sapienza, University of Rome, Rome, ItalyAbstract: The latest development of protein engineering allows the production of proteins having desired properties and large potential markets, but the clinical advances of therapeutical proteins are still limited by their fragility. Nanotechnology could provide optimal vectors able to protect from degradation therapeutical biomolecules such as proteins, enzymes or specific polypeptides. On the other hand, some proteins can be also used as active ligands to help nanoparticles loaded with chemotherapeutic or other drugs to reach particular sites in the body. The aim of this review is to provide an overall picture of the general aspects of the most successful approaches used to combine proteins with nanosystems. This combination is mainly achieved by absorption, bioconjugation and encapsulation. Interactions of nanoparticles with biomolecules and caveats related to protein denaturation are also pointed out. A clear understanding of nanoparticle-protein interactions could make possible the design of precise and versatile hybrid nanosystems. This could further allow control of their pharmacokinetics as well as activity, and safety.Keywords: nanoparticles, drug delivery, proteins, polypeptides, absorption, bioconjugation, encapsulation